Shockwave Treatment Enhanced Extracellular Matrix Production in Articular Chondrocytes Through Activation of the ROS/MAPK/Nrf2 Signaling Pathway. (December 2021) - Shen, Po-Chih; Chou, Shih-Hsiang; Lu, Cheng-Chang; Huang, Hsuan-Ti; Chien, Song-Hsiung; Huang, Peng-Ju; Liu, Zi-Miao; Shih, Chia-Lung; Su, Shu-Jem; Chen, Li-Min; Tien, Yin-Chun
Objective: Shockwave application is a potential treatment for osteoarthritis (OA), but the underlying mechanism remains unknown. Oxidative stress and a counterbalancing antioxidant system might be the key to understanding this mechanism. We hypothesized that reactive oxygen species (ROS) and the transcription factor nuclear factor erythroid 2-related factor 2 (Nrf2), which is an important regulator of cellular redox homeostasis, are plausible elements. Design: Porcine chondrocytes were cultured in a 3-dimensional pellet model and subjected to shockwaves. The effects of shockwaves with various energy-flux densities on optimal extracellular matrix (ECM) synthesis were assessed. ROS, mitogen-activated protein kinase (MAPK) signaling, and the redox activity of Nrf2 were measured. To investigate the signaling mechanism involved in the shockwave treatment in chondrocytes, specific inhibitors of ROS, MAPK signaling, and Nrf2 activity were targeted. Results: Shockwaves increased ECM synthesis without affecting cell viability or proliferation. Furthermore, they induced transient ROS production mainly through xanthine oxidase. The phosphorylation of ERK1/2 and p38 and the nuclear translocation of Nrf2 were activated by shockwaves. By contrast, suppression of ROS signaling mitigated shockwave-induced MAPK phosphorylation, Nrf2 nuclear translocation, and ECM synthesis. Pretreatment of chondrocytes with the specific inhibitors of MEK1/2 and p38, respectively, mitigated the shockwave-induced nuclear translocation of Nrf2 and ECM synthesis. Nrf2 inhibition by both small hairpin RNA knockdown and brusatol reduced the shockwave-enhanced ECM synthesis. Conclusions: Shockwaves activated Nrf2 activity through the induction of transient ROS signaling and subsequently enhanced ECM synthesis in chondrocytes. This study provided fundamental evidence confirming the potential of shockwaves for OA management.